Experimental and computational studies of novel coaxial 2D Bragg structures for a high-power FEM - Konoplev, I; Phelps, A; Cross, A; Ronald, K; McGrane, P; He, W; Whyte, C; Ginzburg, N; Peskov, N; Sergeev, A; Thumm, M (2004)
Two-dimensional (2D) coaxial Bragg structures have been suggested for use in high-power Free Electron Masers (FEM) to synchronize radiation from different parts of an oversized annular electron beam. In this paper, the simulations of field evolution using the three-dimensional code MAGIC are carried out and results are presented. An investigation of 2D Bragg structures obtained by corrugating the inner surface of the outer conductor of a coaxial waveguide or by lining the surface of a smooth waveguide with a dielectric material, which has a bi-periodic permittivity, has been conducted. Experimental studies of 2D Bragg structures were also undertaken and the good agreement between experimental measurements and theoretical predictions is demonstrated. Measurements of a 7cm diameter annular electron beam produced by a high-current accelerator to be used to drive the FEM are presented and the experimental set-up discussed. © 2004 Elsevier B.V. All rights reserved.